Analisis Biaya Produksi dalam Menetapkan Harga Jual yang Kompetitif - Putri, Nanda Utami; Octafian, Ray (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
Based on interviews and analysis, the management of Super Chicken Noodle Eatery conducts comprehensive production cost calculations in determining the selling price. They consider various factors, including raw material costs, labor costs, and factory overhead costs. Additionally, they also take into account external market conditions, such as competitor prices, the level of competition, and consumer preferences. By considering these various factors, the management strives to establish competitive selling prices in the market. However, they face several challenges in the pricing process. One of the main challenges is the unstable fluctuations in raw material prices, which can significantly impact production costs. Additionally, the high level of competition in the local market is also a factor to be considered. Furthermore, the management also struggles with adjusting prices to changes in consumer preferences. Another challenge faced is the increasing factory overhead costs that tend to rise over time. This demands careful and flexible analysis from the management in determining selling prices that remain competitive in the market. Through a comprehensive approach in calculating production costs and considering external factors, the management of Super Chicken Noodle Eatery strives to achieve competitive selling prices in the market while still maintaining profitability.